2017
DOI: 10.1212/wnl.0000000000004123
|View full text |Cite
|
Sign up to set email alerts
|

Multinodular vacuolating and neuronal tumor of the cerebrum

Abstract: A 31-year-old woman presented with chronic headache. MRI revealed an atypical right parietal lesion involving the deep cortical ribbon and adjacent superficial subcortical white matter (figures 1 and 2).There was no enhancement after gadolinium injection. Diffusion-weighted imaging, susceptibilityweighted imaging, and dynamic-susceptibility contrast showed no abnormality. Close follow-up was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 2 publications
5
9
0
Order By: Relevance
“…Since submission of this study, further cases and series have been reported, attesting to the indolent nature of MNVT .…”
Section: Discussionmentioning
confidence: 83%
“…Since submission of this study, further cases and series have been reported, attesting to the indolent nature of MNVT .…”
Section: Discussionmentioning
confidence: 83%
“…It presents as a cluster of nodules, normally numerous and of small size, located juxtacortically on the inner surface of an otherwise normal-appearing cortex and most frequently on the parietal or temporal lobe. Gadolinium enhancement, restricted diffusion, diffuse infiltration, mass effect, or edema is not normally observed [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] .…”
Section: Discussionmentioning
confidence: 96%
“…MNVTs are rare entities that have been recently recognized, by WHO, as distinctive neuronal lesions, although they were first reported by Huse et al, in 10 patients, in 2013 [1] . Since then, 51 additional cases have been reported worldwide [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , including a case series of 33 patients by Nunes et al [9] . MVNT is frequently associated with seizures or seizure equivalents and occur mainly in adults older than 35 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MVNTs are of particular interest to the clinician/epileptologist, not only because of the frequent association with epileptic seizures, but also as an operatively treatable cause of epilepsy. A total of 96 cases (including the current case) have been described in the literature to date (Ratilal et al, 2007;Huse et al, 2013;Bodi et al, 2014;Fukushima et al, 2015;Nagaishi et al, 2015;Yamaguchi et al, 2016;Alsufayan et al, 2017;Badat et al, 2017;Cathcart et al, 2017;Gökç e, 2017;Monté et al, 2017;Nunes et al, 2017;Gonzalez-Quarante et al, 2018;Kapucu et al, 2018;Lobo and Srinivasan, 2018;Pekmezci et al, 2018;Thom et al, 2018) (supplementary table 1), of which 37 were histopathologically verified (HV) (38.54%). A slight female predominance was noticed in both non-HV and HV cases (M:F=2:3 and M:F=9:11, respectively).…”
Section: Discussionmentioning
confidence: 96%